Physics - Giambattista, Alan (McGraw-Hill Higher Education, 2020)
This Physics textbook presents the basic concepts of physics that students need to know for later courses and future careers. This algebra-based text helps students learn that physics is a tool for understanding the real world, and to teach transferable problem-solving skills, that students can use throughout their entire lives. Some of the most important enhancements in this edition include: inclusion of math topic reviews, new/updated MCAT exam coverage added and on online, review and synthesis problems added, new biomedical applications, lists of biomedical applications at the beginning of each chapter, new ranking tasks, checkpoints, and collaborative problems. Connections have also been enhanced to help students see the bigger picture.